Harriet Rouillard: “The Stamp of Its Editor” on the CAAE’s Food for Thought - Leona M. English (Adult Education Research Conference, 2014)
This paper presents the results of an archival study of Harriet Rouillard, editor of the Canadian Association for Adult Education’s journal, Food for Thought, between 1947 and1953. Rouillard’s background, education, and contributions to the association in its early years are discussed.